Socio-Ecological Resilience and the Role of Organizations in Addressing the Complexity of Climate Change in Malaysia - Eka Prastuty (Pemuda Peduli Publikasi Insan Ilmiah, 2025)
Purpose: This study examines how governmental, non-governmental, and community-based organizations in Malaysia contribute to socio-ecological resilience amid climate change. It focuses on identifying organizational strategies, collaborative practices, and key challenges influencing adaptation effectiveness. Subjects and Methods: A qualitative exploratory approach was employed involving 20 participants from governmental agencies, NGOs, and community-based organizations selected through purposive sampling. Data were collected through semi-structured interviews, observations, and document analysis, then analyzed using thematic analysis through open, axial, and selective coding. Results: The findings identified four major themes: organizational awareness and commitment, collaborative approaches, socio-ecological strategies, and institutional challenges. Organizations increasingly integrated climate adaptation into policies and operational practices, while multi-stakeholder collaboration enhanced community participation and knowledge-sharing. Ecosystem-based adaptation and disaster preparedness programs contributed to long-term resilience, although funding limitations, governance fragmentation, and technical constraints remained significant barriers. Conclusions: Socio-ecological resilience in Malaysia depends on institutional commitment, adaptive governance, collaborative engagement, and integrated environmental strategies to address increasingly complex climate challenges.